New Horizons in Patient Safety: Safe Communication: Evidence-based Core Competencies with Case Studies From Nursing Practice - Day, Lisa J.
"This case studies book is an indispensable resource for educators, students, and practitioners of nursing. It is innovative in its application of lessons from the communication sciences to common challenges in the delivery of safe patient care. The authors apply basic tenets of human communication to the context of nursing to provide a foundation for practices that can advance the safety and quality of care. The cases, which describe "close calls" and adverse events, are organized along the continuum of healthcare delivery, providing quick access to solutions in commonly encountered care situations. Each case is accompanied by a discussion of how skillful communication can be key to preventing and recovering from errors and adverse events. Thought-provoking discussion questions and references for further reading make this book a valuable reference for nursing educators, students, and practitioners across the world"--